Peran Keteladanan Pemimpin dalam Membangun Budaya Integritas dan Etika di SMKN 2 Pelaihari - Wafa Nur Azizah; Zurjani Ilmi; Muhammad Fitriadi; Aslamiah Aslamiah; Celia Cinantya (Varied Knowledge Journal, 2026)
This study aims to examine the role of the principal’s exemplary leadership in building a culture of integrity and ethics at SMKN 2 Pelaihari. The study is based on the importance of character development in education, which emphasizes not only academic achievement but also moral and ethical values. This research employed a descriptive qualitative approach. The research subjects consisted of 1 principal, 4 teachers, and 6 students selected purposively based on their involvement in and understanding of the school culture. Data were collected through semi-structured interviews, participatory observation, and documentation, and then analyzed using an interactive analysis model. The findings show that the principal’s exemplary leadership played a significant role in shaping a culture of integrity through three main mechanisms: providing direct examples in daily behavior, maintaining consistency between words and actions, and transmitting values through interactions among the principal, teachers, and students. In addition, the culture of integrity was strengthened through habituation programs and character-building activities involving the entire school community. However, several challenges were identified, including differences in individual character and varying levels of awareness among school members. This study concludes that exemplary leadership is an effective strategy for building an ethical and integrity-based organizational culture and has important implications for strengthening values-based leadership in education.